Pharmacy education in Saudi Arabia: Achievements and challenges during the last two decades with a focus on Taif University as a case study - Fathelrahman, Ahmed Ibrahim; Alrobaian, Majed; Altowayan, Waleed Mohammad; Maghrabi, Ibrahim; Asiri, Yousif A (Saudi pharmaceutical journal, 2022)
Basic expectation from graduates of any pharmacy program is to be able to provide pharmaceutical care at both patients and community levels, be able to solve problems arising during practice, be able to improve quality and outcomes of the services provided continuously and be able to respond effectively to patients and community changing needs. Pharmacy education in Saudi Arabia established in 1959 by founding the first college in Riyadh (King Saud University) followed by establishing two pharmacy colleges in Jeddah (King Abdulaziz University, 2001) and Abha (King Khalid University, 2001), then a college in Al Ahsa (King Faisal University, 2002), followed by four colleges three-years later in each of Buraydah (Qassim University, 2005), Madinah (Taibah University, 2005), Taif (Taif University, 2005) and Makkah (Umm Al-Qura University, 2005). Up to date the number of pharmacy colleges offering basic degrees in pharmacy are 21 governmental and eight privates. This review describes pharmacy education in Saudi Arabia, the historical perspective, current situation, and the important features. The report focuses on the changes during the last two decades covering three main aspects (1) Clinical education and training, (2) Research output, and (3) Quality and accreditation.Basic expectation from graduates of any pharmacy program is to be able to provide pharmaceutical care at both patients and community levels, be able to solve problems arising during practice, be able to improve quality and outcomes of the services provided continuously and be able to respond effectively to patients and community changing needs. Pharmacy education in Saudi Arabia established in 1959 by founding the first college in Riyadh (King Saud University) followed by establishing two pharmacy colleges in Jeddah (King Abdulaziz University, 2001) and Abha (King Khalid University, 2001), then a college in Al Ahsa (King Faisal University, 2002), followed by four colleges three-years later in each of Buraydah (Qassim University, 2005), Madinah (Taibah University, 2005), Taif (Taif University, 2005) and Makkah (Umm Al-Qura University, 2005). Up to date the number of pharmacy colleges offering basic degrees in pharmacy are 21 governmental and eight privates. This review describes pharmacy education in Saudi Arabia, the historical perspective, current situation, and the important features. The report focuses on the changes during the last two decades covering three main aspects (1) Clinical education and training, (2) Research output, and (3) Quality and accreditation.